Further development of expert system for friction stir welding - Lee, Huai Qin (2017)
Welding is available in diverse forms where the range of applications can spread from manufacturing a component to an aircraft. One of such welding would be the Friction Stir Welding (FSW). In this report, Friction Stir Welding (FSW) of aluminium alloys that was invented in 1991 will be reviewed. The basic principles of FSW consisting the methods used, the process parameters are explained. The welding positions that are available in FSW are also been discussed. The increase advance of technology leads to an increase efficiency of welding. Hence, the quality of weld will then be associated as a key factor and therefore standard is used to benchmark this quality. Therefore, in FSW each of the aspects must comply with ISO standard, ISO 25239: Friction Stir Welding-Aluminium. The scope and elements that are involved in ISO 25239 were studied before developing an expert system related to FSW to comply with ISO standard. To organize the elements in ISO standard and make them into practical use, the software, FileMaker was chosen to develop the expert system. Functions of the application were explained. Terms and conditions before certifying a qualified welding operator are illustrated in the application. Despite the fact of all these study, there are still rooms remain to be explored about the process and further development are analyzed.